Contemporary Ulum al-Qur’an as a Foundation for Strengthening Religious Moderation - Ali, Zahra Sajid (International Conference on Islamic Studies, 2025)
This study examines the role of Contemporary Ulum al-Qur’an as a foundational framework for strengthening religious moderation in the modern context. In an era marked by ideological polarization, extremism, and misinterpretations of religious texts, Ulum al-Qur’an offers methodological principles that ensure a balanced, contextual, and holistic understanding of the Qur’an. This research employs a qualitative library-based approach by analyzing classical and contemporary scholarly works related to Ulum al-Qur’an, thematic interpretation, and maqāṣid al-Qur’ān. The findings reveal that contemporary approaches to Ulum al-Qur’an—such as thematic exegesis, contextual analysis, and maqāṣid-oriented interpretation—play a significant role in promoting values of tolerance, justice, balance, and coexistence. Furthermore, these approaches help prevent literalist and extremist readings of the Qur’anic text by emphasizing ethical objectives and socio-historical contexts. This study concludes that Contemporary Ulum al-Qur’an is not only relevant but also essential in developing a moderate religious discourse capable of addressing contemporary social and humanitarian challenges.